1973
DOI: 10.1007/bf01950234
|View full text |Cite
|
Sign up to set email alerts
|

Etude des residus d'evaporation de solutions d'hydrogenocarbonates de calcium et de magnesium

Abstract: (Re~u le 2 mars 1972)Residues from the evaporation of pure or mixed solutions of Ca(HCO3)2 and Mg(HCO3)2 were subjected to investigation by DTA (N 2 or CO2 atmosphere), TG, EGA, X-ray and classical chemical analysis. The Ca/Mg atomic ratio exerted a great effect on EGA and DTA peaks between 400 and 500 ~ Peak temperatures were the lowest when 1.2 < Ca/Mg < 1.33. When Ca/Mg < 1.25, CaCO8 exists only as aragonite. When Ca/Mg > 1.25, calcite progressively replaces aragonite, but never entirely. Investigations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…In the thermoanalytical studies by Ramamurthy and Secco [11] and Pannetier et al [8-1, brochantite was found to decompose to dolerophanite between 250 and 400 ~ but no formation of antlerite was reported. Vandael and Vanthournhout [18] studied the copper patina obtained in urban atmospheres which mainly consists of brochantite by thermal analysis and reported that antlerite is formed at 280-380 ~ which is converted to dolerophanite between 415 and 550 ~ Brochantite minerals from the Soviet Union [19] also showed the formation of dolerophanite around 530 ~ which finally gave copper oxide around 900 ~ In this study, however, the presence of dolerophanite could not be detected at any stage of the decomposition of brochantite, either by X-ray diffraction or by infrared spectroscopy. This is also substantiated during DTA beyond 700 ~ by the absence of any endothermic peak corresponding to the decomposition of dolerophanite.…”
Section: Resultsmentioning
confidence: 98%
“…In the thermoanalytical studies by Ramamurthy and Secco [11] and Pannetier et al [8-1, brochantite was found to decompose to dolerophanite between 250 and 400 ~ but no formation of antlerite was reported. Vandael and Vanthournhout [18] studied the copper patina obtained in urban atmospheres which mainly consists of brochantite by thermal analysis and reported that antlerite is formed at 280-380 ~ which is converted to dolerophanite between 415 and 550 ~ Brochantite minerals from the Soviet Union [19] also showed the formation of dolerophanite around 530 ~ which finally gave copper oxide around 900 ~ In this study, however, the presence of dolerophanite could not be detected at any stage of the decomposition of brochantite, either by X-ray diffraction or by infrared spectroscopy. This is also substantiated during DTA beyond 700 ~ by the absence of any endothermic peak corresponding to the decomposition of dolerophanite.…”
Section: Resultsmentioning
confidence: 98%
“…Belgian researchers [17] studied the decomposition of Ca, Mg(HCOa)2 using the combination DTA-EGA. Others [18] used a similar combination for investigations of the decomposition of sodium and calcium dithionate-hydrates.…”
Section: Development Of Instrumentsmentioning
confidence: 99%
“…Observations are presented in conCa nection with the valueof the ~gg ratio in the solution, and crystallization of MgCO3 or its absence during thermolysis. Some of these are interpreted.L'int6r~t pr6sent6 par cette 6tude en ce qui concerne la connaissance de la composition des r6sidus d'6vaporation a d6jh 6t6 mis en 6vidence dans une de nos publications antdrieures [1].I1 a d6j/~ 6t6 montr6 ~t cette occasion que le comportement thermique des compos6s carbonat6s du magn6sium 6tait responsable de la difficult6 d'interprdtation des courbes ATD et TG de ces r6sidus d'dvaporation. …”
unclassified